Evaluating an Adjunctive Mobile App to Enhance Psychological Flexibility in Acceptance and Commitment Therapy. (November 2017) - Levin, Michael E.; Haeger, Jack; Pierce, Benjamin; Cruz, Rick A.
The primary aims of this study were to evaluate the feasibility and potential efficacy of a novel adjunctive mobile app designed to enhance the acquisition, strengthening, and generalization of acceptance and commitment therapy (ACT) skills being taught in therapy. A sample of 14 depressed/anxious clients receiving ACT used the ACT Daily app for 2 weeks in a pre–post, open trial design. Participants reported a high degree of program satisfaction. Clients significantly improved over the 2-week period on depression and anxiety symptoms as well as a range of psychological inflexibility measures. Analyses of mobile app data indicated effects of ACT Daily skill coaching on in-the-moment measures of inflexibility and symptoms, with unique effects found for acceptance and mindfulness. Adjunctive ACT mobile apps appear promising in enhancing therapy effects on psychological inflexibility and outcomes. A tailored skill coaching approach like ACT Daily based on randomly prompted assessments may be especially promising.